47.3k views
19 votes
Is this correct? if not please show correct version step by step.

Is this correct? if not please show correct version step by step.-example-1

1 Answer

5 votes

Step/Answer:

The mistake begins at the line 3 where distrubting 2 in the expression. line 1 and line 2 both are correct. But line 3 is wrong.


2 {x}^(2) + 2x - 2 = 2 {x}^(2) - 18 \\ 2 {x}^(2) + 2x - 2 - 2 {x}^(2) + 18 = 0 \\ 2x - 2 + 18 = 0 \\ 2x + 16 = 0 \\ 2x = - 16 \\ x = - 8


2( {x}^(2) - 9) = (2 * {x}^(2) ) + (2 * ( - 9)

From line 3, you forgot to distribute 2 in -9.

User Jun HU
by
5.2k points